Como se traduz no âmbito do Direito Comparado? Reflexões a partir de casos práticos - Pietroluongo, Márcia Atalla (Language and Law / Linguagem e Direito, 2016)
Comparative lawyers are daily faced with the need to translate in order to compare, although they are not professional translators. One can thus wonder whether Comparative Law can contribute to the eld of Legal Translation and how, especially by studying how these lawyers overcome (or fail to do so) translational and comparative obstacles that they are faced with, and by examining the procedures applied to study and describe foreign legal systems. This article aims to unveil the most relevant translational procedures used in four publications of ve volumes in the eld of Comparative Law, which seek to introduce, disseminate and deepen the knowledge of Brazilian Law among French lawyers and conversely the knowledge of French Law among Brazilian lawyers.